UNFPA-UNICEF Global Programme to Accelerate Action to End Child Marriage in Zambia (2016-2019) - Br Munthe, Arta Salesta; Farid, Muhammad (Global Strategis, 2024)
Child marriage is a prevalent phenomenon in developing countries, especially in sub-Saharan Africa. Zambia is one with the highest rate of child marriages, with 1.7 million child brides. This study investigates the contribution of UNICEF (United Nations Children's Fund) and UNFPA (United Nations Population Fund) to cope with child marriage issues in Zambia through the Global Program to End Child Marriage (GPECM). The writer employs the concept of Human Security as an analytical tool in addressing the risk of child marriage in Zambia. This article next explains the role of UNICEF and UNFPA as international organizations in handling human security cases in Zambia. The final result of the study revealed that UNICEF and UNFPA contributed significantly to handling child marriage cases as a human security issue in Zambia by empowering adolescent girls, advocating for policy, providing assistance to enhance the quality of social services, and creating guidance to address the challenges. Keywords: Child Marriage, Human Security, GPECM, UNICEF, UNFPA  Perkawinan anak merupakan fenomena umum di negara-negara berkembang, terutama di sub-Sahara Afrika. Zambia adalah salah satu negara dengan tingkat pernikahan anak tertinggi di dunia dengan 1,7 juta pengantin perempuan kategori anak. Studi ini mengkaji kontribusi UNICEF (Dana Anak-Anak Perserikatan Bangsa-Bangsa) dan UNFPA (Dana Penduduk Perserikatan Bangsa-Bangsa) dalam mengatasi isu perkawinan anak di Zambia melalui Global Program to End Child Marriage (GPECM). Penulis menggunakan konsep Keamanan Manusia (Human Security) sebagai alat analisis dalam menangani risiko perkawinan anak di Zambia. Penulis selanjutnya menjelaskan peran UNICEF dan UNFPA sebagai organisasi internasional yang berinisiatif menangani kasus keamanan manusia di Zambia. Hasil akhir penelitian mengungkapkan bahwa UNICEF dan UNFPA berkontribusi secara signifikan dalam menangani kasus perkawinan anak sebagai isu keamanan manusia di Zambia dengan memberdayakan anak perempuan, mengadvokasi kebijakan, memberikan bantuan untuk meningkatkan kualitas layanan sosial, dan membuat panduan penanganan khusus atas kasus tersebut. Kata-kata Kunci: Pernikahan Anak di Zambia, Keamanan Manusia, GPECM, UNICEF, UNFPA